Evaluation of the consumption of psychotropic substances by students in the health area: Portrait of a decade (Research, Society and Development, 2020)
In recent years, the rates of consumption of psychotropic drugs in the Brazilian population have increased exorbitantly, thus characterizing a worrying fact for the country. Despite the positive therapeutic perspective that these drugs bring to the population in the face of various psychological health problems as well as anxiety disorders, their negative results are also relevant data that must be evaluated. Psychotropics act on the central nervous system, changing behavioral patterns, however, it is important to highlight that in addition to the side effects caused, the abusive use can cause chemical dependence. We searched the SciELO, ScienceDirect and Pubmed databases for review articles and originals, involving the theme “university students in the health area” linked to “consumption of psychotropics”. Original articles and review papers addressing the theme from 2007 to 2017 were considered, which presented, in addition to other drugs, psychotropic substances, and disregarded those that did not include students in the health area, and did not deal with psychotropic drugs. The data were grouped statistically and placed in tables. It was possible to observe that male students were more susceptible to use, it is also possible to observe that alcohol consumption among students is the item with the highest percentage, since it is a legal drug, easily incorporated into the most diverse drinks, in addition to be socially accepted. It is possible to conclude that the stress generated by the academic routine linked to social factors, can lead the student to have more contact with these substances.